Intensification of a fermentation process for producing lactic acid in a ceramic membrane combined bioreactor system - Fan, Rong; Ebrahimi, Mehrdad; Aden, Matthias; Czermak, Peter (My University, 2013)
A membrane-based filtration process could efficiently reduce the cost of lactic acid production, which is mainly due to its downstream separation and purification steps. In order to achieve high-volumetric productivity of lactic acid, ceramic micro (MF)- and ultrafiltration (UF) membranes are selected to separate the lactic acid from the fermentation broth. For a successful combination of separation unit and fermentation system, membranes should be characterized separately for the determination of membrane performance and the impact of process parameters on it. In this work, the statistical design of experiment was explored to investigate the effects of the physical properties of fermentation broth (cell density, glucose concentration) and process parameters of filtration (transmembrane pressure (TMP) and tangential flow velocity (CFV)) on membrane performances (flux and membrane fouling). In the meantime, the cell density was tracked with the scattered light sensor (FAUDI Aviation AFGUARD®), which is designed for in situ measurement of particulate matters and firstly developed for online control of biotechnical processes. Under the application of AFGUARD® sensor in the filtration process the cell rejection could be online monitored efficiently and economically. The results indicated that the 50 nm and 100 kDa membranes had the better performances (higher flux and lower fouling) in comparison to the other membranes (0.2 μm and 20 kDa) under the same operating condition. Biomass was successfully remained in retentate and not found in permeate. In the further experiments, the filtration unit will be integrated to the bioreactor system in order to establish a continuous fermentation process in which cell growth kinetics, lactic acid productivity and membrane performance will be studied.
Keywords: Ceramic membrane; Transmembrane pressure; Tangential flow velocity; Online monitoring; Lactic acid